2018
DOI: 10.1016/j.ccell.2018.01.002
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting the Senescence-Overriding Cooperative Activity of Structurally Unrelated H3K9 Demethylases in Melanoma

Abstract: SUMMARY Oncogene-induced senescence, e.g., in melanocytic nevi, terminates the expansion of pre-malignant cells via transcriptional silencing of proliferation-related genes due to decoration of their promoters with repressive tri-methylated histone H3 lysine 9 (H3K9) marks. We show here that structurally distinct H3K9-active demethylases—the lysine-specific demethylase-1 (LSD1) and several Jumonji C domain-containing moieties (such as JMJD2C)—disable senescence and permit Ras/Braf-evoked transformation. In mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
113
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(120 citation statements)
references
References 69 publications
7
113
0
Order By: Relevance
“…Importantly, miR‐24‐2‐dependent miR‐6079 increased the level of tri‐methylation of histone lysine (H3K9me3) by inhibiting of JMJD2A. Studies have reported that H3K9me3 modification in the promoter region of the gene can affect the transcriptional activity of some genes . Our results also confirmed that miR‐24‐2 increased the H3K9me3 loading on the oncogene pim 1 promoter region, thereby promoting the expression of Pim1, indicating that the change of H3K9me3 modification triggered by miR‐24‐2 is beneficial to the growth of cancer cells at least in hepatoma cell Hep3B.…”
Section: Discussionsupporting
confidence: 81%
“…Importantly, miR‐24‐2‐dependent miR‐6079 increased the level of tri‐methylation of histone lysine (H3K9me3) by inhibiting of JMJD2A. Studies have reported that H3K9me3 modification in the promoter region of the gene can affect the transcriptional activity of some genes . Our results also confirmed that miR‐24‐2 increased the H3K9me3 loading on the oncogene pim 1 promoter region, thereby promoting the expression of Pim1, indicating that the change of H3K9me3 modification triggered by miR‐24‐2 is beneficial to the growth of cancer cells at least in hepatoma cell Hep3B.…”
Section: Discussionsupporting
confidence: 81%
“…5a, b). Furthermore, p16 INK4A , a critical OIS tumor suppressor and senescence mediator, and H3K9me3, a marker of senescence-associated heterochromatic foci 28,29 . Both of them were significantly repressed by the absence of Men1 in both KMS and Men1 Δ/Δ mice (Fig.…”
Section: Loss Of Menin Triggers Aberrant Dna Damage Responsementioning
confidence: 99%
“…7b). 2-PCPA-1a, an inhibitor of LSD1, promotes oncogenic BRAF mutation-induced OIS in melanoma cells 29 . IR exposure elicited obvious SA-β-gal staining in IMR-90 cells (51.9%) that was eliminated by MI-3 (30.0%) but markedly increased by exposure to SP2509 (95.4%) ( Supplementary Fig.…”
Section: Lsd1 Inhibitor Reverses Ne Differentiation In Lung Cancersmentioning
confidence: 99%
“…and PTPN6 have been shown to regulate CS in human cell lines, and will be added to build 2 of CellAge (Sun et al, 2015;Yu et al, 2018).…”
Section: Unweighted Rna-seq Co-expression Networkmentioning
confidence: 99%